LEARNING MODULE DEVELOPMENT MATHEMATICS LOADED CULTURE WEAVING BAMBOO FOR INCREASE THINK CRITICAL STUDENTS OF MADRASAH ALIYAH NEGERI (MAN) 1 KERINCI - Elvina Asmi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Study This aiming For know How develop module learning mathematics loaded culture wicker bamboo For increase think critical student Madrasah Aliyah Negeri (MAN) 1 Kerinci. Methods research used​ is study development (research and development). The model used in development This is the ADDIE model. The results of the study show that module learning developed mathematics​ have effectiveness with very critical category reviewed from aspect give explanation simple, build skills basis, conclude, give explanation continue, and set strategies and tactics. On the ability think after given learning with use module obtained​ score 82.28% with very critical category. Can concluded that ability think critical student after use module mathematics loaded culture wicker bamboo six meetings​ is very critical.